Implementasi Pewarnaan Graf Menggunakan Metode Algoritma Tabu Search Pada Penjadwalan Kerja Perawat - Rina Filia Sari; Fibri Rakhmawati; Nur Lela (G-Tech: Jurnal Teknologi Terapan, 2023)
Scheduling the work of nurses, especially nursing in hospitals, is often a problem faced by every hospital. This is because there are many problems and there are limitations that must be met. So far, RSUD Drs. H. Amri Tambunn still uses the manual method in compiling the nurse's work schedule so that he often experiences difficulties and the resulting work schedule is still uneven and regular. This scheduling problem can be solved by coloring the graph nodes. One of the algorithms for solving graph vertex coloring problems in scheduling is the Tabu Search Algorithm. The Tabu Search algorithm is a method of solving combinatorial optimization problems. This method aims to streamline the process of finding the best solution to a problem. So i can get the conclusion that Tabu Search Algorithm can be applied to solve the problem of scheduling nurses in hospitals, one of which is in Drs RSUD. H. Amri Tambunan. Application of Node coloring by using Taboo Search results in more efficient nurse scheduling where there is no clashing schedule , meaning no nurse gets two shifts on the same day.